Word and music studies : essays on performativity and on surveying the field (Word and music studies ;, 2011)
The main section of this volume of essays addresses the topic of 'Performativity in Literature and Music', a subject of high contemporary relevance since a substantial part of recent reflections in the humanities are concerned with the performance aspect of cultural activities, particularly in the arts. This decisive reorientation of scholarly interests in the arts, trendily called the 'performative turn', has yielded significant contributions to an increasingly refined understanding of artistic processes from an up-to-date perspective, and specifically what has been called the 'crisis of the work concept' has sharpened our awareness of the need of finding the 'proper' object of such scholarly investigations, which, as in most traditional studies, cannot be exclusively the written documents of our cultural heritage, but additionally, and essentially so, their actualizations in performance situations. This volume for the first time offers a set of careful case studies from a wide range of artistic genres (narrative fiction, poetry, opera, instrumental music, songs, jazz) and historical phases (from Elizabethan verse to 21st-century HD opera performances) which give detailed insight into consequences of addressing issues of performativity in the field of word and music studies. Closely examined examples range, in music, from the romantic reception of Bach and the opera singer Maria Malibran through Mahler and Schoenberg to Brigitte Fassbaender, Philip Glass and Charles Mingus, and, in literature, from Sidney through Yeats and Celan to Katherine Mansfield, Alejo Carpentier and Toni Morrison. In addition, the volume contains a smaller section on 'Surveying the Field' of word and music studies which includes an essay of general reflection on interart relationships and an attempt at identifying new features of the 'musicalization of fiction'. This collection of essays will be relevant to students and scholars from a wide variety of fields: performance studies, intermediality studies, art theory, musicology, voice studies, literary criticism, and philosophy.